Comparative Study of Boron Precursors for Chemical Vapor‐Phase Deposition‐Grown Hexagonal Boron Nitride Thin Films. Issue 3 (9th July 2020) - Yamada, Hisashi; Inotsume, Sho; Kumagai, Naoto; Yamada, Toshikazu; Shimizu, Mitsuaki
Abstract : Two different boron precursors, diborane (B2 H6 ) and trimethyl boron ((CH3 )3 B, TMB), are investigated for chemical vapor‐phase deposition (CVD)‐grown hexagonal boron nitride ( h ‐BN) on α‐Al2 O3 (0001) substrates. The BN layer grown using TMB includes a large amount (2 × 10 20 cm −3 ) of carbon atoms, which is 60 times higher than that in the BN layer grown using B2 H6 . The X‐ray diffraction 2 θ / ω scans for BN film grown using B2 H6 exhibit the h ‐BN (002) peak. The BN film obtained using TMB includes turbostratic BN ( t ‐BN). The E2g Raman peak frequencies in B2 H6 and TMB h ‐BN are observed at 1368.8 and 1369.7 cm −1, respectively. The Raman peak shift to a higher frequency indicates that a larger compressive strain is induced using TMB than using B2 H6 . The full width at half maximum of the B2 H6 and TMB Raman peak frequencies is 21.8 and 42.7 cm −1, respectively. The cathodoluminescence spectra of B2 H6 h ‐BN show the band‐edge emissions at 225 and 232 nm, whereas only a 300 nm broadband is obtained in TMB h ‐BN. It is suggested that the carbon atoms in TMB prevent the formation of highly crystalline h ‐BN thin films. Abstract : Two different boron precursors, diborane (B2 H6 ) and trimethyl boron ((CH3 )3 B, TMB), are investigated for chemical vapor‐phase deposition (CVD)‐grown hexagonal boron nitride ( h ‐BN) on α‐Al2 O3 (0001) substrates. The BN layer grown using TMB includes a large amount (2 × 10 20 cm −3 ) of carbon atoms, which is 60 times higher than that in the BN layer grown using B2 H6 .